Effect of Dialysis Day on Intradialytic Hypotension Risk - Ana Rocha; Clemente Sousa; Paulo Teles; Augusto Coelho; Eva Xavier (Karger Publishers, 2016)
Background/Aims: Intradialytic hypotension (IDH) is a serious and frequent complication of hemodialysis (HD). Thus far, data are scarcely available to assess the impact of first versus subsequent HD sessions of the week in IDH. Therefore, the purpose of this work was to evaluate IDH risk in patients on thrice-weekly HD. Methods: We conducted an analysis of all blood pressure (BP) measurements obtained during 492 HD treatments given to 41 prevalent adult patients over a one month period. A logistic regression model for repeated binary observations was used to determine the association between hypotension and patient and dialysis factors. Results: The incidence of IDH was 32.5%. First dialysis session of the week was associated with a 9% higher risk of hypotension relatively to the second one. The risk was even higher from the first to the third session of the week (60%) and from the second to the third (50%). A higher hypotension odds ratio was also associated with age (1.03, 90%CI: 1.01-1.06), higher predialysis BP (1.04, 90%CI: 1.03-1.05) and higher phosphorus level (1.38, 90%CI: 1.07-1.76). The risk decreased 24.4% for each additional antihypertensive drug taken by the patient. Conclusions: The odds of hypotension occurrence decrease throughout dialysis sessions of the week. Minimizing modifiable risk factors may decrease IDH episodes.